Thermodynamics of Supramolecular Associations with Macrocyclic Water-Soluble Hosts - Garnier, Ludovic (ACS Omega, 2019)
[Image: see text] The thermodynamic study of the complexation of the β-cyclodextrins and p-sulfonatocalix[n]arenes (CnS) with the 4-aminoazobenzene was reported and was carried out by molecular dynamics simulations. We determined the whole thermodynamic properties (K, Δ(r)G°, Δ(r)H°, and TΔ(r)S°) using the potential of mean force (PMF) technique and more precisely the adaptive biasing force method. Depending on both the nature of the host molecule and the pH of the solution, the PMF profiles present different shapes and energy minima. Considering the complexity of these PMF profiles, we are also interested in the structural properties of these associations. Hence, we calculated hydrogen bonds, Lennard-Jones and electrostatic energies, the number of atoms of the guest molecule inserted inside the cagelike host molecule, and the number of water molecules expelled from the cavity.